2011
DOI: 10.1007/s11999-010-1587-y
|View full text |Cite
|
Sign up to set email alerts
|

Neurocentral Synchondrosis Screws to Create and Correct Experimental Deformity: A Pilot Study

Abstract: Background Unilateral pedicle screw epiphysiodesis of the neurocentral synchondrosis (NCS) can produce asymmetric growth of the synchondrosis to create scoliosis in an immature animal model. Questions/purposes We asked whether a preexisting experimentally created scoliosis could be limited and corrected by modulating the growth of the faster-growing NCS by a similar method. Methods Nine 1-month-old pigs were assigned to each of three groups: (1) a sham group in which three animals received a sham operation but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…The curves obtained in this study are opposite to that found by using selective epiphysiodesis of the neurocentral cartilage, that is convex toward the non‐instrumented side. The curves obtained by neurocentral cartilage blocking show consistently the convexity toward the side of screw fixation …”
Section: Discussionmentioning
confidence: 62%
“…The curves obtained in this study are opposite to that found by using selective epiphysiodesis of the neurocentral cartilage, that is convex toward the non‐instrumented side. The curves obtained by neurocentral cartilage blocking show consistently the convexity toward the side of screw fixation …”
Section: Discussionmentioning
confidence: 62%
“…Historically, several investigators have investigated the feasibility of fusion‐less surgery in treating immature idiopathic scoliosis, yet only a few studies actually tested the correction power using large animal models . Recently, a porcine model which induces a moderate spinal curve by posterior spinal and concave rib tethering was developed .…”
Section: Discussionmentioning
confidence: 99%
“…Their findings suggested that injury to the NCC by pedicle screw insertion results in iatrogenic spinal stenosis (20 to 25 % narrowing). Zhang et al [6] reported that either unilateral or bilateral pedicle screws disturbed spinal canal growth in 4-week-old pigs resulting in narrowing of the hemi-canal area on the epiphysiodesis side. Pedicle screws have an influence on the development of symmetry and the canal parameters [32].…”
Section: Discussionmentioning
confidence: 99%
“…When a pedicle screw is inserted in the immature spine, penetration through the NCC is inevitable, which thus has raised a major concern regarding whether the passage of a pedicle screw through the NCC will affect the development of the growing spine. Some authors have postulated that pedicle screw instrumentation might cause damage to the NCC in the immature spine, leading to the inadequate development of the spinal canal, resulting in iatrogenic spinal stenosis [4][5][6]. In contrast, other authors maintain that pedicle screws can be safely placed in pediatric patients without a negative influence on the growth of the pedicles and the spinal canal [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%